2016
DOI: 10.1093/geronb/gbw073
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Patterns Among Older Couples: Longitudinal Associations With Negative Marital Quality

Abstract: The present findings stress the importance of considering the drinking status rather than the amount of alcohol consumed of both members of the couple when attempting to understand drinking and marital quality among older couples. These findings are particularly salient given the increased drinking among baby boomers and the importance of marital quality for health among older couples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…Our results add to a growing body of literature emphasizing that the longitudinal effects of alcohol use can best be understood in a dyadic context by focusing on concordance between partners (Birditt et al, 2016;Homish & Leonard, 2007). However, our findings also suggest another qualification: The role of couple context itself might be shaped by a larger community context.…”
Section: Alcohol Use Must Be Understood In All Of Its Contextssupporting
confidence: 60%
See 1 more Smart Citation
“…Our results add to a growing body of literature emphasizing that the longitudinal effects of alcohol use can best be understood in a dyadic context by focusing on concordance between partners (Birditt et al, 2016;Homish & Leonard, 2007). However, our findings also suggest another qualification: The role of couple context itself might be shaped by a larger community context.…”
Section: Alcohol Use Must Be Understood In All Of Its Contextssupporting
confidence: 60%
“…While assortative mating research has demonstrated that individuals are more likely to form relationships with others with similar levels of drinking (e.g., Agrawal et al., ; Grant et al., ; Hall, Hesselbrock, & Stabenau, ), there still can be couples with sizable differences in drinking frequency and quantity between partners. Longitudinal studies with dyadic data have suggested that such drinking discrepancies predicted deterioration in relationship quality while more matched levels of drinking were associated with sustained satisfaction (Birditt, Cranford, Manalel, & Antonucci, ; Homish & Leonard, ). A more detailed analysis of such “drinking partnerships” in a sample of 647 couples near the start of marriage suggested that couples with either heavy husband drinking or couples where both the husband and wife drank heavily but rarely in each other's presence demonstrated lower concurrent relationship satisfaction compared to couples where both spouses drank frequently and together (Roberts & Leonard, ).…”
Section: The Varying Effects Of Alcohol Use On Romantic Relationshipsmentioning
confidence: 99%
“…also acknowledged remaining questions about ‘the specific factors and mechanisms that contribute to these latent genetic and environmental correlations’. Recent extensions of the APIM focusing on cognitive and behavioral mediators of associations between alcohol use and marital outcomes have been advanced , and the availability of large dyadic data sets that include genetic and substance use data offers the opportunity to test dyadic hypotheses about genetic and environmental influences on alcohol and marital outcomes. In addition, a recently advanced social‐attributional model of alcohol reinforcement suggests possible mechanisms for the effects of relationship processes on alcohol use.…”
mentioning
confidence: 99%
“…Two recent studies using data from the Health and Retirement Study in the USA showed the importance drinking health behavior concordance has on the quality of marriage, an important factor affecting health in general, and also suggested that higher partner mastery belief (self-efficacy) is associated with better self-rated health and fewer functional limitations. 10,12 A common understanding between spouses regarding a need for change might be pivotal for the success of promoting healthy attitudes and behaviors. Future research using a longitudinal design aiming to deepen knowledge about the effect of each spouse's behavior on the other is required, especially in low-and middleincome countries.…”
Section: Discussionmentioning
confidence: 99%
“…11 Regarding drinking behavior specifically, another study also using data from the Health and Retirement Study in the USA showed that couples in which both spouses drank reported decreased negative marital quality, and that this effect was greater for wives than husbands. 12 These studies focused on older couples, but only in high-income countries, and very little is currently known about older couples' health behavior concordance in low-and middle-income countries, where aging is occurring at a rapid rate. To address this knowledge gap, we used population-based studies on older people from Cuba, the Dominican Republic, Mexico, Puerto Rico and Peru to estimate the concordance in couples for two important health behaviors (drinking and smoking), tested if these rates were beyond chance and examined potential factors associated with these concordances.…”
Section: Introductionmentioning
confidence: 99%